1994
DOI: 10.1084/jem.179.3.961
|View full text |Cite
|
Sign up to set email alerts
|

The expression of the interleukin 6 gene is induced by the human immunodeficiency virus 1 TAT protein.

Abstract: SummaryHuman immunodeficiency virus 1 (HIV1) infection is associated with severe psoriasis, B cell lymphoma, and Kaposi's sarcoma. A deregulated production of interleukin 6 (IL-6) has been implicated in the pathogenesis of these diseases. The molecular mechanisms underlying the abnormal IL-6 secretion of HIVl-infected cells may include transactivation of the IL-6 gene by HIV1.To test this hypothesis, we used the plL6Pr-chloramphenicol acetyltransferase (CAT) plasmid, an IL-6 promoter-CAT construct, as a target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
114
0
3

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(119 citation statements)
references
References 46 publications
(87 reference statements)
2
114
0
3
Order By: Relevance
“…Indeed, it was shown that Tat induces the expression of several cytokines, such as tumor necrosis factor, 42 interleukin-2, 43 interleukin-6, 33,44 and transforming growth factor-␤. 45 The nature of the cooperation between BKV TAg and Tat protein in the pathogenesis of the lesions appearing in BKV/tat transgenic mice seems to be mainly related to the transcriptional activation of tat promoter by BKV TAg, which is a potent transactivator of the HIV-1 LTR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it was shown that Tat induces the expression of several cytokines, such as tumor necrosis factor, 42 interleukin-2, 43 interleukin-6, 33,44 and transforming growth factor-␤. 45 The nature of the cooperation between BKV TAg and Tat protein in the pathogenesis of the lesions appearing in BKV/tat transgenic mice seems to be mainly related to the transcriptional activation of tat promoter by BKV TAg, which is a potent transactivator of the HIV-1 LTR.…”
Section: Discussionmentioning
confidence: 99%
“…23,30 Experimental evidence also indicates that Tat regulates the expression of cellular genes, modulating cell functions. [31][32][33] Tat is highly angiogenic in vivo, 30,34 and transgenic mice expressing the tat gene develop skin lesions closely resembling the early phases of KS. 35,36 In a previous study, transgenic mice were generated by means of a recombinant DNA (pRPU3R-Tat) containing BKV early region and the HIV-1 tat gene, directed by the HIV-1 long terminal repeat (LTR).…”
mentioning
confidence: 99%
“…43,44 It is known that the TAT protein can transactivate inflammatory host genes, 45 including the IL-6 gene. 46 It is plausible that the transactivation of IL-6 gene causes activation of the C3 promoter, which can explain the higher background levels found with the C3-Tat/HIV two-component system as compared to our IL-1/IL-6 construct (Figures 7 and 9). It must be emphasized that the basal transgene levels and the fold induction using the C3-Tat/HIV two-component system were far better in adenoviral-transfected HepG2 cells and in primary rat synovial fibroblasts.…”
Section: Discussionmentioning
confidence: 82%
“…In vivo studies have shown that Tat deregulates the expression levels of several cytokines (Scala et al, 1994;Westendorp et al, 1994;Bannasser & Bahraoui, 2002). By using a vector expressing IL-6 under the control of the IL-6 promoter, it has been demonstrated that Tat transactivates the human IL-6 promoter (Scala et al, 1994).…”
Section: Tat-induced Modulation Of Cellular Gene Expressionmentioning
confidence: 99%